Vitamin E and protection of DNA, proteins and lipids from oxidative damage: evaluation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006. (14th October 2016) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen‐Ildico; Mangelsdorf, Inge; McArdle, Harry; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from Specialised Nutrition Europe (formerly IDACE), submitted for authorisation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of France, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to vitamin E and protection of DNA, proteins and lipids from oxidative damage. The Panel considers that vitamin E is sufficiently characterised and that protection of DNA, proteins and lipids from oxidative damage is a beneficial physiological effect. The target population proposed by the applicant is infants (from birth) and young children up to 3 years of age. The Panel has previously assessed a claim on vitamin E and protection of DNA, proteins and lipids from oxidative damage with a favourable outcome. The target population was the general population. The Panel considers that the role of vitamin E in protection of DNA, proteins and lipids from oxidative damage applies to all ages, including infants and young children up to 3 years of age. The Panel concludes that a cause and effect relationship has been established between the dietary intake of vitamin E and protection of DNA, proteins and lipids from oxidative damage.